The 'n-3 LC-PUFA sparing effect' of modified dietary n-3 LC-PUFA content and DHA to EPA ratio in Atlantic salmon smolt - Mohamed Codabaccus; Christopher Carter; Andrew Bridle; Nichols, PD (2012)
n−3 Long-chain (≥C 20 ) polyunsaturated fatty acids (LC-PUFA) are used extensively by fish via β-oxidation when in dietary surplus. Therefore it is of interest to optimize n−3 LC-PUFA deposition in fish via a reduction in β-oxidation which may be induced by manipulation of dietary fatty acids. This study tested whether Atlantic salmon smolt fed a dietwith a higher docosahexaenoic acid (DHA):eicosapentaenoic acid (EPA) ratio and a lower content of n−3 LC-PUFA to that of fish oil (FO) based diets would enhance deposition of n−3 LC-PUFA in fish tissues. Comparisons were made between fish fed: a FO diet, a blend of 50% rapeseed and 50% tuna oil diet (model oil, MO 1), a blend of 50% rapeseed, 25% tuna and 25% FO diet (MO 2), and a blend of 50% FO and 50% chicken fat diet (FO/CF). The dietary DHA:EPA ratio was in the order MO 1>MO 2>FO/CF~FO. Dietary n−3 LC-PUFA content was approximately 2-fold lower in fish fed the MO 1, MO 2 and FO/CF diets compared to the FO diet. There were comparable amounts of n−3 LC-PUFA in the muscle of FO,MO1 and FO/CF fed fish. Our findings indicate that the right balance in both absolute and relative amounts of EPA and DHA can promote n−3 LC-PUFA retention.